PD-L1 gene amplification and focality: relationship with protein expression. Issue 2 (27th February 2023) - Jardim, Denis Leonardo; Murugesan, Karthikeyan; Elvin, Julia A.; Huang, Richard S. P.; Kurzrock, Razelle
Abstract : PD-L1 (CD274) amplification occurs in a small subset of malignancies and may predict anti-PD-1/PD-L1 immunotherapy responsiveness. We hypothesized that both copy number (CN) and focality of cancer-related PD-L1 amplifications impact protein expression, and, thus, analyzed solid tumors that underwent comprehensive genomic profiling between March 2016 and February 2022 at Foundation Medicine. PD-L1 CN alterations were detected using a comparative genomic hybridization-like method. PD-L1 CN changes were correlated with PD-L1 protein expression (DAKO 22C3 antibody) by immunohistochemistry (IHC). Overall, 60, 793 samples were analyzed (most frequent histologies: lung adenocarcinoma (20%), colon adenocarcinoma (12%), lung squamous carcinoma (8%)). Using a definition of CD274 CN ≥ specimen ploidy +4 (6 copies), 1.21% of tumors (738/60, 793) were PD-L1 amplified. Focality category distribution was as follows: <0.1 mB (n=18 (2.4%)), ≥0.1 to <4 mB (n=230 (31.1%)), ≥4 to <20 mB (n=310 (42%)), ≥20mB (n=180 (24.4%)). Lower levels of PD-L1 amplification (below specimen ploidy +4) were more frequently non-focal amplifications compared to higher levels. In addition, more focal amplification (<0.1 mB) correlated with higher PD-L1 IHC expression. Median tumor proportion score (TPS) for samples with PD-L1 amplification (ploidy ≥+4) according to focality were 87.5% (<0.1 mB), 80% (≥0.1 to <4 mB), 40% (≥4 to <20 mB), 1% (≥20mB). In specimens with PD-L1 ploidy less than +4, but highly focal (<0.1 mB), the 75th percentile of PD-L1 expression by TPS was 80%. Conversely, non-focal (≥20 mB) PD-L1 amplification (ploidy ≥+4) can present high PD-L1 expression (TPS≥50%), albeit infrequently (0.09% of our cohort). In conclusion, PD-L1 expression measured by IHC is influenced by PD-L1 amplification level and focality. Further correlation between amplification, focality, protein expression and therapeutic outcome for PD-L1 and other targetable genes warrants exploration.